CANDLE Syndrome: Case Report of a Rare Type of Auto- Inflammatory Disease (Bangladesh Journal of Child Health, 2021)
CANDLE syndrome (chronic atypical neutophilic dermatosis with lipodystrophy and elevated temperature) is an autoinflammatory disease/syndrome characterized by recurrent fever, skin lesions, and multisystem inflammatory manifestations. Most of the patients have shown mutation in PSMB8 gene. Here, we report a 9-year-old girl with recurrent fever, atypical facies, widespread skin lesions, generalized lymphadenopathy, hepato-splenomegaly, lipodystrophy, and failure to thrive. Considering the clinical features and laboratory investigations including skin biopsy findings, diagnosis was consistent with CANDLE syndrome. Therefore, it is recommended to consider CANDLE syndrome in a young child who presents with recurrent fever, characteristics rashes, organomegaly and failure to thrive.Bangladesh J Child Health 2020; VOL 44 (3) :174-177